Physics event photo analysis module based on the STEM approach: An effort to enhance critical thinking - Maryani, Maryani; Yuliana, Yasmin; Anggraeni, Firdha Kusuma Ayu (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2021)
This research aimed to determine the validity of the Physics Event Photo Analysis (AFKF) module based on the STEM approach and improve students' critical thinking skillsat SMA Negeri 1 Rogojampi. The researchers implemented the ADDIE development model to achieve these goals, which consisted of five stages: Analysis, Design, Development, Implementation, and Evaluation. The data collecting techniques used in this research were interviews, product validation, and tests. The validation results indicated that the product was feasible to use with a validity percentage of 93%. The percentages can be categorized as very valid and can be used without revision. Furthermore, the percentage of the product's effectiveness in improving students' critical thinking abilitywas 66.58% which was included in the medium category. The PhysBased on the STEM approach, the Event Photo Analysis Module (AFKF) based ed positive responses from students with a percentage of 76%.TThis development research concluded that the STEM approach-based Physics Event Photo Analysis (AFKF) module is very valid and effective in improving students' critical thinking skills.